Threatened Plants of Scania, Sweden - Joel Levin (GBIF Sweden, 2026)
The threatened plants of Scania, Sweden collection is a curated collection of plants collected from known relic localities around Scania, often in collaboration with local authorities and always with correct permissions, of plants that are threatened according to the Swedish Red List. The plants are grown and shown at the Lund University Botanical Garden with the purpose of building up a genetic bank for eventual restoration efforts (that is conservation ex situ and eventually in situ).
Keywords: Skåne; conservation; Sweden; Threatened Plants; Occurrence; Specimen; OCCURRENCE; Biological Sciences; Biologi